KEBIJAKAN SELEKSI DALAM MENDUKUNG STANDAR KOLEKSI DI PERPUSTAKAAN SEKOLAH - Suryanto, Suryanto (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2021)
The school library is a library in a school to support the teaching and learning activities and objectives of the parent school. In terms of the collection, the library has a standard, both from the number of collections as well as the depth of the collection. There needs to be the selection policy as part of a collection development policy so that these standards are fulfilled. This paper uses literature study method. This paper provides guidance to the school librarian about the things that need to be considered in making the selection policy. Selection policy must consider the amount of collection, type of collection, the suitability of the curriculum, language, and so forth.